Acoustic emission energy b-value for local damage evaluation in reinforced concrete structures subjected to seismic loadings. (1st March 2018) - Sagasta, Francisco; Zitto, Miguel E.; Piotrkowski, Rosa; Benavent-Climent, Amadeo; Suarez, Elisabet; Gallego, Antolino
Highlights: A modification of the original acoustic emission b -value is proposed. The modification is based on the use of the energy of the AE signals. Evolution of the energy b -value indicates the onset of severe damage. The severe damage was concentrated at the beam-column connections. Abstract: A modification of the original b -value (Gutenberg-Richter parameter) is proposed to evaluate local damage of reinforced concrete structures subjected to dynamical loads via the acoustic emission (AE) method. The modification, shortly called energy b -value, is based on the use of the true energy of the AE signals instead of its peak amplitude, traditionally used for the calculation of b -value. The proposal is physically supported by the strong correlation between the plastic strain energy dissipated by the specimen and the true energy of the AE signals released during its deformation and cracking process, previously demonstrated by the authors in several publications. AE data analysis consisted in the use of guard sensors and the Continuous Wavelet Transform in order to separate primary and secondary emissions as much as possible according to particular frequency bands. The approach has been experimentally applied to the AE signals coming from a scaled reinforced concrete frame structure, which was subjected to sequential seismic loads of incremental acceleration peak by means of a 3 × 3 m 2 shaking table. For this specimen two beam-column connections—one exterior and one interior—were instrumented with wide band low frequency sensors properly attached on the structure. Evolution of the energy b -value along the loading process accompanies the evolution of the severe damage at the critical regions of the structure (beam-column connections), thus making promising its use for structural health monitoring purposes.